Sensitivity of patient-specific physiological and pathological aortic hemodynamics to the choice of outlet boundary condition in numerical models - Tianai Wang; Christine Quast; Florian Bönner; Tobias Zeus; Malte Kelm; Teresa Lemainque; Ulrich Steinseifer; Michael Neidlin (Computer Methods and Programs in Biomedicine Update)
Purpose: Outlet boundary conditions (OBC) play a pivotal role in all simulations of vascular flow. However, previous investigations of OBC impact on numerical aortic flow simulations were not yet comprehensive for the entirety of hemodynamic characteristics. They mainly investigated near-wall properties and velocity in physiological flow. Therefore, the aim of this work was to expand the sensitivity assessment to hemodynamic markers in the bulk flow to the choice of OBC for a physiological and pathological aortic flow field. Material and methods: Image-based computational models of subject-specific aortic geometries were created. Temporally and spatially resolved inlet velocity profiles derived from 4D Flow MRI were implemented. Three types of OBCs were compared: zero pressure, loss coefficients and three-element Windkessel. Their influence on velocity, near-wall properties and bulk flow quantities were analyzed. Results: Velocity and near-wall parameters in the ascending aorta are largely insensitive to the OBC choice. However, bulk flow parameters, in particular the helicity field, are highly sensitive throughout the entire aortic domain with differences of up to 600 % between models. The relative sensitivity to OBC drops for pathological flows, as the influence of more complex inlet profiles increases. Conclusion: While the sensitivity of velocity and near-wall parameters to OBC choice is insignificant when only the ascending aorta is assessed, our study proposes a more thorough discernment once bulk flow parameters are of interest. Different degrees of boundary condition complexity are required to determine the hemodynamic properties of interest accurately. A support tool is presented to determine the case-dependent minimum requirement for inlet and outlet boundary conditions.